1995
DOI: 10.1126/science.267.5196.367
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of Surfactants on Nanostructured Palladium Clusters by a Combination of STM and High-Resolution TEM

Abstract: Scanning tunneling microscopy (STM) and high-resolution transmission electron microscopy (TEM) have been used to determine the dimensions of a series of palladium clusters stabilized by tetraalkylammonium salts. Electrochemically prepared colloids were used in which the average diameter of the inner metal core was varied between 2 and 4 nanometers, and the size of the ammonium ions was adjusted in the series (+)N(n-C(4)H(9))(4) < (+)N(n-C(8)H(17))(4) < (+)N(n-C(18)H(37))(4). The difference between the mean dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
178
0
4

Year Published

1998
1998
2014
2014

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 345 publications
(190 citation statements)
references
References 26 publications
8
178
0
4
Order By: Relevance
“…In a seminal paper based on the combined use of transmission electron and scanning tunneling microscopies, the group of M. Reetz demonstrated that these metal nanoparticles possess a core-shell structure in which the metallic core is stabilized by a monolayer of tetra alkylammonium species, and the thickness of this shell is linearly correlated with the length of the alkyl chains. 19 In the last decade, the electrolytic production of nanoparticles and nanocomposites containing platinum group elements has been extensively studied, due to the strong catalytic properties of these products. 13 ,zQ-25 The electro-synthesis of Cu and Ag colloids, on the other hand, has been the subject of only a few reports.…”
Section: -18mentioning
confidence: 99%
“…In a seminal paper based on the combined use of transmission electron and scanning tunneling microscopies, the group of M. Reetz demonstrated that these metal nanoparticles possess a core-shell structure in which the metallic core is stabilized by a monolayer of tetra alkylammonium species, and the thickness of this shell is linearly correlated with the length of the alkyl chains. 19 In the last decade, the electrolytic production of nanoparticles and nanocomposites containing platinum group elements has been extensively studied, due to the strong catalytic properties of these products. 13 ,zQ-25 The electro-synthesis of Cu and Ag colloids, on the other hand, has been the subject of only a few reports.…”
Section: -18mentioning
confidence: 99%
“…During the process, the cell was kept under a nitrogen atmosphere. Since in these systems the NPs shell thickness is roughly proportional to the chain length of the surfactant (Reetz and Helbig, 1994;Reetz et al, 1995), while the core size is mainly influenced by the electrochemical parameters, Au NPs with a shell thickness of about 1.2 nm were synthesized using TOAC. The working potential was set at +1 V corrosion voltages and the electrolysis charge at 300 mC.…”
Section: Electrochemical Synthesis Of Au Npsmentioning
confidence: 99%
“…Electrochemical methods [19][20][21][22] were used to produce transition metal nanoparticles whose size can be controlled by adjusting the current density. In this type of synthesis, tetraalkylammonium salts were used as both supporting electrolyte and stabilizer for the cluster formed.…”
Section: Introductionmentioning
confidence: 99%